Associations between COVID-19 outcomes and asthmatic patients with inhaled corticosteroid - Yong, Su-Boon; Gau, Shuo-Yan; Li, Chia-Jung; Tseng, Chih-Wei; Wang, Shiow-Ing; Wei, James Cheng-Chung (Frontiers in Pharmacology, 2023)
Background: The impact of inhaled corticosteroid (ICS) in the interaction between asthma, COVID-19 and COVID-19 associated outcomes remain largely unknown. The objective of this study is to investigate the risk of COVID-19 and its related outcomes in patients with asthma using and not using inhaled corticosteroid (ICS). Methods: We used the TriNetX Network, a global federated network that comprises 55 healthcare organizations (HCO) in the United States, to conduct a retrospective cohort study. Patients with a diagnosis of asthma with and without ICS between January 2020 and December 2022 were included. Propensity score matching was used to match the case cohorts. Risks of COVID-19 incidence and medical utilizations were evaluated. Results: Out of 64,587 asthmatic patients with ICS and without ICS, asthmatic patients with ICS had a higher incidence of COVID-19 (Hazard ratio, HR: 1.383, 95% confidence interval, CI: 1.330–1.437). On the contrary, asthmatic patients with ICS revealed a significantly lower risk of hospitalization (HR: 0.664, 95% CI: 0.647–0.681), emergency department visits (HR: 0.774, 95% CI: 0.755–0.793), and mortality (HR:0.834, 95% CI:0.740–0.939). In addition, subgroup or sensitivity analyses were also conducted to examine the result of different vaccination status, disease severity, or COVID-19 virus variants. Conclusion: For asthmatic patients using ICS, risk of COVID-19 was significantly higher than non-users. The observed association could provide potential guidance for primary care physicians regarding the risk of COVID-19 in asthmatic patients.